On proposing relational environmental metaphors to stimulate engagement and foster well-being in the midst of climate change - Bellehumeur, Christian R.; Carignan, Laure-Marie (Frontiers in Psychiatry, 2024)
Messages regarding climate change that are intended to stimulate responsible engagement can impact our mental health in both positive and negative ways, which in turn can increase or limit the potential engagement being sought through those very messages. Increasingly alarmist environmental metaphors are being brought into question due to their possibly detrimental impact on mental health and well-being, and in their place, relational environmental metaphors are proffered to instill hopeful and constructive individual and collective engagement for responsible climate action. This article discusses how both alarmist and relational environmental metaphors interact with eco-emotions. It proposes, in light of concepts arising from Porges' Polyvagal Theory -on the psychophysiology of autonomic states created in contexts of threatening cues and feelings of safety and connection -, that relational environmental metaphors are preferable for stimulating responsible collective engagement and fostering global well-being in the midst of climate change.